PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM - Yolanda Husna, Febby; Franshisca Sihombing, Sarmauli (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Maternal deaths occur after childbirth in around 60% of cases, and postpartum obstetric care with monitoring eliminates 50% of these deaths. The puerperium is a critical time for mothers. Breast milk is essential for preserving an infant's health and survival. Breastfeeding should begin as soon as possible, ideally in the first 30 to 60 minutes following delivery.The goal of the baby's suction on the mother's nipple is not to extract a large amount of milk. Soy milk or soy beans are commonly available and reasonably priced, and they can facilitate a smoother nursing experience. This study aimed to ascertain whether providing soy milk to postpartum moms could enhance their supply of breast milk. In this work, a case study methodology was combined with descriptive research techniques. Mrs. "D," who is receiving care at Hj. Bunda Halimah Hospital in Batam City, has an enhanced milk production that is measured by using observation sheet with LATCH scores. The results of the study after being given soy milk 2 times in 3 consecutive days with a LATCH score of 9 (good). The conclusion of midwifery care in postpartum mothers by giving soy milk times in 3 consecutive days has an effect on increasing Mrs. D's milk production